Prevalence and factors Associated with alcohol Use in selected urban communities in Ibadan, Nigeria (2023)
Nigeria is ranked high among African countries in the consumption of alcohol and the national adult per capita consumption was estimated at 12.3litres. Harmful alcohol use is the sixth leading cause of disability and deaths in Nigeria. This study assessed the prevalence and factors associated with alcohol use in selected urban communities in Ibadan, Nigeria. This community-based cross sectional study was conducted among 500 respondents in two selected urban communities in Ibadan, Nigeria. The World Health Organization STEPS tool was used to collect data on socio-demographic characteristics of respondents and the history of alcohol use. Alcohol users were categorized into ever consumed, current consumers, consumers within last 12 months, and frequent consumers within 30 days (low, medium, and high consumers).Chi-square analysis was used to identify factors associated with the different categories of alcohol consumption. The mean age of the respondents was 35.36_12.24 years. Almost one third of the participants (29.0%) reported they had ever consumed alcohol and (13.6%) had consumed alcohol within 30 days prior to the study. Factors significantly associated with the ever-use of alcohol were gender (p¼0.000), and income (p¼0.000). Current use of alcohol had a statistically significant relationship with male gender (p¼0.000). The prevalence of high alcohol use is low in the sample of urban communities studied, and factors influencing include sex, marital status, level of education, income. These results should inform policy decisions to address the alcohol use in urban communities in Southwest Nigeria.